PERANAN ILO MELALUI PROYEK PROPEL (PROMOTING RIGHTS AND OPPORTUNITIES FOR PEOPLE WITH DISABILITIES IN EMPLOYMENT THROUGH LEGISLATION)-INDONESIA DALAM MEMPROMOSIKAN HAK KESEMPATAN KERJA BAGI PARA PENYANDANG DISABILITAS DI INDONESIA - Fitria Budi Widya Hanny (Global Political Studies Journal, 2017)
This study aims to determine the role and efforts of the ILO in promoting the rights of persons with disabilities employment opportunities in Indonesia in 2012-2014. This study used qualitative methods, with the data collection technique literature (online searches, interviews, documentation). As for analyzing the data, researchers used data reduction techniques. The results showed that the role carried out by the ILO through PROPEL project-Indonesia in promoting the rights of persons with disabilities employment opportunities in Indonesia serves as a platform and means. ILO helps, socialize, approach, providing technical assistance and recommend solutions or policies in dealing with disability issues against the government, employers and labor unions in Indonesia. The conclusion from this study is the ILO has contributed to promoting the rights of persons with disabilities employment opportunities in Indonesia, is viewed from many policy makers began raising the issue of disability in providing employment opportunities to Indonesian people with disabilities and priorities Disability Bill for the Government of Indonesia today.